RETRACTION Torres Aguilar, X. (2023). , De lo emocional a lo social. La Neuroeducación en la Educación Física desde los Estudios Regionales(From emotional to social. Neuroeducation in Physical Education from Regional Studies),. Retos, 47, 523–530. https://doi.org/10.47197/retos.v47.94675 - RETOS, RETOS (Retos, 2025)
Torres Aguilar, X. (2023). , De lo emocional a lo social. La Neuroeducación en la Educación Física desde los Estudios Regionales(From emotional to social. Neuroeducation in Physical Education from Regional Studies),. Retos, 47, 523–530. https://doi.org/10.47197/retos.v47.94675 Retraction of the article by the editor of the journal. Failure to comply with the obligation to pay the fee once accepted for publication.